Practice nurses' experiences of the Care plus programme: A qualitative descriptive study - Henty, Catherine M. (Auckland University of Technology, 2005)
This qualitative descriptive study using thematic analysis describes the experience of practice nurses in caring for people with chronic health conditions using the Care Plus programme. In taking on this new role practice nurses have had to adjust to ‘a new way of working’, ensuring they are ‘being prepared’ adequately and ‘have enough time’. This programme also involves ‘a new approach for patients’ in response to increased nursing input into their care. The findings of this study suggest that the Care Plus programme offers practice nurses the opportunity to practice in an expanded role to improve the health outcomes of people with chronic health conditions. To ensure success in this new role, practice nurses need to have adequate training and education as well as support from their colleagues within the General Practice.
Keywords: New Zealand Ministry of Health; Care plus; Primary nursing; Chronically ill care